Sustainable Land Management and Technology Adoption in Eastern Uganda - Woelcke, Johannes; Berger, Thomas; Park, Soojin (International Food Policy Research Institute, 2006)
Under the regimes of Idi Amin (1971–79) and Milton Obote (1980–85), Uganda’s economy plunged into a prolonged crisis with negative real growth rates of GDP (Baffoe 2000). In 1987, under Yoweri Musevini, the Ugandan government introduced an economic recovery program in cooperation with the IMF and the World Bank, aiming at market liberalization, privatization, and de-centralization. Although these reforms have had positive effects on the Ugandan economy (the GDP real growth has averaged 6 percent per annum), productivity in the agricultural sector has either stagnated or declined (APSEC 2000). Land degradation is generally seen as a major factor contributing to declining agricultural productivity as well as to poverty and food insecurity. Recent studies in eastern and central Uganda have revealed high negative nutrient balances for most cropping systems (Wortmann and Kaizzi 1998).